Suspected pulmonary embolism in patients with pulmonary fibrosis: Discordance between ventilation/perfusion SPECT and CT pulmonary angiography. Issue 6 (7th April 2016) - Leuschner, Gabriela; Wenter, Vera; Milger, Katrin; Zimmermann, Gregor S.; Matthes, Sandhya; Meinel, Felix G.; Lehner, Sebastian; Neurohr, Claus; Behr, Jürgen; Kneidinger, Nikolaus
Abstract: Background and Objective: Pulmonary embolism (PE) is a common differential diagnosis in patients with pulmonary fibrosis presenting with a clinical deterioration. Both ventilation/perfusion (V/Q)‐single photon emission computed tomography (SPECT) and computed tomographic pulmonary angiography (CTPA) are routinely used to detect PE. However, the value of V/Q‐SPECT and CTPA in this scenario has not been studied so far. We aimed to investigate the concordance of V/Q‐SPECT and CTPA in patients with pulmonary fibrosis and suspicion of pulmonary embolism. Methods: A total of 22 consecutive patients with pulmonary fibrosis and clinical deterioration who underwent both V/Q‐SPECT and CTPA were included in the study and analyzed for the presence of pulmonary embolism. Results: Nine of 22 patients (41%) had evidence for pulmonary embolism in V/Q‐SPECT, and two of these patients had matching evidence for pulmonary embolism in CTPA. In the other seven patients with positive findings in V/Q‐SPECT, no evidence of pulmonary embolism was found in CTPA. None of the 13 patients with a negative V/Q‐SPECT had evidence for pulmonary embolism in CTPA. Conclusion: In patients with pulmonary fibrosis and suspected pulmonary embolism, pulmonary embolism is detected more frequently by V/Q‐SPECT than by CTPA. Thromboembolic disease is identified on CTPA only in a minority of patients with positive findings on V/Q‐SPECT. When making treatment decisions, clinicians should be aware of the high rate of discordant findings in V/Q‐SPECT and CTPA in this specific patient population. Abstract : The purpose of the study was to investigate the concordance of V/Q‐SPECT and CTPA in patients with pulmonary fibrosis and suspicion of pulmonary embolism. V/Q‐SPECT resulted in substantially more positive results than CTPA. When making treatment decisions, clinicians should be aware of the high rate of discordant findings.